(3EOGQI GdUQGYGJ hGdCReGJ aj GdeDSSI GdGbJUGOjIs - (3LjdGdj(B, (3bGdhfs ((3GdLRGFQ(B:s (3OGQ GdcJGH GdYQHj(B,s, 2017)
(3ebOeI YGeI, OQGSI hJMdjd GdeMjW GdNGQLj hGdOGNdj ddeDSSI GdGbJUGOjI, EOGQI GdUQGY GdJfXjej, GdGWGQ GdeaGgjej dg, hCSHGHg, heQGMd GdUQGY GdJfXjej, cPdc eSJhjGJg hGdBKGQ hGdGSJQGJjLjGJ GOGQI GdUQGY GdJfXjej, hGdefgL GdGSdGej aj GdJYGed eY GdUQGYGJ, HGdEVGaI Edi EOGQI GdCReGJ, eONd YGe Mhd CReGJ aj GdeDSSGJ, hGOGQJgGhGdfehPL GdGSdGej dEOGQI GdCReGJ, hCNjQG GdEOGQI HGdCReGJ(B.s
(3eQGLY U(B.156 s
Keywords: (3GdCReGJ GdGbJUGOjIs